Association of serum levels of inflammatory cytokines with retinopathy of prematurity in preterm infants - Ling, Xiao Chun; Huang, Pin-Hsuan; Chen, Hung-Chi; Hsueh, Yi-Jen; Lee, Chia-Wen; Lien, Reyin; Lee, Chien-Chung; Chu, Shih-Ming; Chen, Kuan-Jen; Hwang, Yih-Shiou; Lai, Chi-Chun; Chiang, Ming-Chou; et al. (Frontiers in Pediatrics, 2024)
Introduction: Retinopathy of prematurity (ROP) is a retinal vascular developmental disease associated with risks factors such as supplementary oxygen use or low birth weight/early gestational age. Multiple studies have reported associations between ROP and systemic inflammation. In this study, we investigated serum cytokines associated with ROP development and severity and assessed their applicability as potential biomarkers of ROP.Methods: This prospective study was conducted at an institutional referral center between 2019 and 2021. To measure the serum levels of 40 inflammatory cytokines in eligible premature patients, we collected their serum samples during the enrollment of patients or the intravitreal injection of antivascular endothelial growth factor (VEGF) agents and after 2 and 4 weeks.Results: Fifty patients were enrolled. In patients with type 1 ROP who received anti-VEGF agents (n = 22), the levels of serum intercellular adhesion molecule-1 decreased significantly (p < 0.05) at 4 weeks compared with the baseline level, whereas those of serum granulocyte-macrophage colonystimulating factor increased significantly (p < 0.05). In patients with ROP who did not require any treatment (n = 14), no significant change was noted in the level of any of the 40 inflammatory cytokines. In control infants without ROP (n = 14), the serum levels of tumor necrosis factor-α, interleukin (IL)-15, and IL-12p40 increased significantly (p < 0.05) at 4 weeks. The changes in the levels of serum inflammatory cytokines did not vary significantly among the aforementioned three groups. A generalized estimating equation indicated that zone 1 ROP, stage 3 ROP, older postmenstrual age, respiratory distress syndrome, necrotizing enterocolitis, and sepsis were associated with the changes in serum cytokine levels.Conclusions: Although significant changes (compared with baseline) were observed in the serum levels of certain inflammatory cytokines in patients with type 1 ROP and infants without ROP, no significant difference in cytokine level fluctuations were noted among the three groups. Changes in serum inflammatory cytokine levels may not predict ROP development or severity. Additional comprehensive studies are warranted to establish their definitive role and significance in ROP, emphasizing the need for continued research in this area.